Perancangan Model Bisnis Berdasarkan Komparatif Dua Fitness Center Untuk Meningkatkan Jumlah Pelanggan - Made Setini; Ida Bagus Teddy Prianthara (Jurnal Manajemen dan Bisnis, 2018)
ABSTRACTThe purpose of this research is to create a new Business Fitness Center design model based on customer perception on the competitive advantage of Celebrity Fitness and Hawa Gym by using Canvas Model then analyzed with SWOT Analysis approach, which will produce new Business Canvas Model.This is a qualitative research, which can be done as an attempt to find, develop, test the truth and seek back a knowledge premises using scientific methods, Source data used in this study obtained from field observation and interviews of informants directly related to the problems which researched in this case is the Fitness manager, Instructure, and Member who move in both Gym. Data Analyst provided by identifying ongoing business using 9 elements of canvas model next in doing SWOT analysis. The results of the study were compared of the two fitness sites described with the new Canvas Model Image.